Video‐Assisted Thoracoscopic Surgery (VATS) Versus Thoracotomy in the Treatment of Pulmonary Hydatid Cysts: A Randomized Controlled Trial - Fahmi H. Kakamad (Health Science Reports)
ABSTRACT Background and Aims Pulmonary hydatid cysts (PHC), resulting from infection by Echinococcus granulosus larvae, represent a substantial health risk in livestock‐raising areas, often causing respiratory symptoms and even death. The primary treatment for PHC involves surgical excision, either through open thoracotomy or video‐assisted thoracoscopic surgery (VATS). However, the superiority of one method over the other remains debatable. The present study aims to compare VATS and thoracotomy outcomes in managing PHC. Methods A trial involving 50 patients was conducted to compare VATS and thoracotomy in managing PHCs. Randomization was implemented, and data collection was performed in a blinded manner. Descriptive and regression analyses were utilized to evaluate the data and find potential confounders. Results Patient data were almost evenly distributed across groups. The VATS group had lower postoperative pain levels and return time to work in comparison to those who underwent open thoracotomy. It reached a significant difference in correlation analysis. However, other factors such as age, sex, comorbidities, smoking status, and the size and number of cysts exhibited minimal correlations. Conclusion This randomized controlled trial indicates that VATS may provide benefits in alleviating postoperative pain and expediting the resumption of work activities. However, larger‐scale studies are necessary to provide comprehensive clinical recommendations.